Foreign direct investment in developing countries : the case of Latin America (The Institute MadridES, 1994)
Analyses foreign direct invest (FDI) flows to the developing world. Reviews recent developments and the associated methodological obstacles to analysis. Evaluates the macroeconomic, microeconomic and policy-related factors involved, making use of inter-regional comparisons. Addresses the impact of FDI on aspects of the local economy in Latin America and assesses the policy alternatives, particularly for Latin America.
Located in the Office of the Secretary-General